Cover Picture: Switching of Single‐Molecule Magnetic Properties of TbIII–Porphyrin Double‐Decker Complexes and Observation of Their Supramolecular Structures on a Carbon Surface (Chem. Eur. J. 36/2014). Issue 36 (1st September 2014) - Inose, Tomoko; Tanaka, Daisuke; Tanaka, Hirofumi; Ivasenko, Oleksandr; Nagata, Toshi; Ohta, Yusuke; De Feyter, Steven; Ishikawa, Naoto; Ogawa, Takuji
<x xml:space="preserve">Abstract</x> Switching of the magnetic properties of single‐molecule magnets (SMMs) consisting of octaethylporphyrin (OEP)–TbIII double‐decker complexes has been achieved. Three different electronic forms—protonated, anionic, and radical—of the (OEP)–TbIII complex have been synthesized and magnetic susceptibility measurements revealed that only the anionic and radical forms exhibit SMM properties, allowing on/off switching between the forms. All three complexes form an isomorphic pseudo‐hexagonal 2D pattern when dropcast onto a carbon surface, regardless of the differences in the electronic structures of their porphyrin–Tb cores. For more details, see the Full Paper by D. Tanaka, T. Ogawa et al. on page 11362 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>